Wireless local area network: a comprehensive review of attacks and metrics - Sarvari, Samira; Sani, Nor Fazlida Mohd; Hanapi, Zurina Mohd; Abdullah, Mohd Taufik (Asian Research Publication Network, 2017)
Wireless Local Area Networks (WLAN) was once a single network solution. Yet now, it contributes to all part of business and computer industry. Thus, WLAN security measures need special attention. In order to identify WLAN networks’ vulnerability, some intrusion detection systems, architecture, and potential threats in the literature of this area is investigated. This approach is to categorize present wireless intrusion detection system (IDS) and detection technique. Several advantageous and drawbacks are presented and an in-depth critical literature review is presented. Different WLAN attack types and review some metrics in relation to operability and performance of IDS is summarized and extensively argued which can be conducted through integrating both practitioners and scholars. The future research areas are also discussed.